2014
DOI: 10.1177/0884533614546168
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Status of Patients With Chronic Hepatitis B or C

Abstract: Overweight/obesity is prevalent among patients with hepatitis B and C and can contribute to the development of steatosis. Malnutrition is also observed and is related to the severity of liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
(16 reference statements)
1
3
0
Order By: Relevance
“…In this present study was possible analyzed the anthropometric parameters of risk identification to cardiovascular diseases in patients diagnosed with hepatitis C. The majority of patients were female, similarly as observed by Menta et al (2015) in which 54.0% of hepatitis C patients were female. Regarding the lifestyle evaluation, this present research evidenced a high rate of physical inactivity.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In this present study was possible analyzed the anthropometric parameters of risk identification to cardiovascular diseases in patients diagnosed with hepatitis C. The majority of patients were female, similarly as observed by Menta et al (2015) in which 54.0% of hepatitis C patients were female. Regarding the lifestyle evaluation, this present research evidenced a high rate of physical inactivity.…”
Section: Discussionsupporting
confidence: 53%
“…According to Petta (2017) a pro-inflammatory and pro-fibrogenic environment increases even more the development of cardiovascular lesions. Thus, due to metabolic alterations and extrahepatic manifestations observed in patients, it is common to observe overweight in these individuals (Menta et al, 2015). Alves, Schmidt and Benet (2018) evidence that the high percentage of body fat observed in chronic hepatitis C patients is considered as an important risk factor to the appearance of CVD and other associated complications.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis C virus (HCV) affects approximately 170 million people worldwide, and complications associated with chronic hepatitis C (CHC) include liver fibrosis, cirrhosis, liver failure, and hepatocellular carcinoma (HCC) . Malnutrition has been identified in 13.0% to >90.0% of patients with liver disease . Altogether, these conditions contribute to loss of muscle mass (MM), an important indicator of malnutrition.…”
mentioning
confidence: 99%
“…Malnutrition has been identified in 13.0% to >90.0% of patients with liver disease. 2,3 Altogether, these conditions contribute to loss of muscle mass (MM), an important indicator of malnutrition. A recent cross-sectional study from National Health Examination and Nutrition (NHANES) demonstrated that low MM, as assessed by mid-upper arm circumference (MUAC) measurements, precedes the development of cirrhosis in patients with CHC.…”
mentioning
confidence: 99%